Copper metabolism patterns and tumor microenvironment characterization in colon adenocarcinoma - Lin, Jianwei; Luo, Bixian; Yu, Xinbo; Yang, Zheyu; Wang, Mingliang; Cai, Wei (Frontiers in Oncology, 2022)
Copper participates in biological processes such as oxygen metabolism and iron uptake, and is a key factor in immune regulation. Based on the transcription data, mutation data and clinical data of colon adenocarcinoma (COAD) patients from The Cancer Genome Atlas (TCGA) database and Gene Expression Profiling Interactive Analysis (GEPIA2) database, the expression and mutation of copper metabolization-related genes in COAD patients and their correlation with tumor immune microenvironment were analyzed. Copper metabolization-related genes (CMRGs) were used to construct COAD subtypes, and prognostic risk models were constructed. Furthermore, Kaplan-Meier (K-M) curve and ROC curve were used to analyze the clinical value of COAD subtypes and genotyping models in distinguishing clinical characteristics of patients, and the immune infiltration of patients with different genotypes was analyzed. Finally, the clinical tissue samples from COAD patients were used to analyze the mRNA expression of genes in risk model between tumor and normal tissues by the method of Polymerase Chain Reaction (PCR). Of the 479 CMRGs, 68 genes were differentially expressed in normal and tumor tissues of COAD patients in TCGA and GEPIA2. Two subtypes with different clinical and immunological characteristics were identified by using 482 genes related to copper metabolism. Finally, a prognostic risk model consisting of five CMRGs was constructed, which could not only predict the prognosis of patients, but also correlated with COAD subtypes. In addition, some genes (GSTM1, CCND1 and CYP2S1) in risk model was show significant difference between normal and tumor tissues. The two different COAD subtypes identified by CMRGs can help clinically distinguish patients with different prognosis and tumor progression, and the risk score can assist in clinical evaluation of patient prognosis, serving as a valuable biomarker for COAD immunotherapy.